2017
DOI: 10.3389/fimmu.2017.00418
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response of Mouse Thymic Epithelial Cell Types to Ionizing Radiation-Induced DNA Damage

Abstract: Thymic epithelial cells (TECs) are the main components of the thymic stroma that support and control T-cell development. Preparative regimens using DNA-damaging agents, such as total body irradiation and/or chemotherapeutic drugs, that are necessary prior to bone marrow transplantation (BMT) have profound deleterious effects on the hematopoietic system, including the thymic stroma, which may be one of the main causes for the prolonged periods of T-cell deficiency and the inefficient T cell reconstitution that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…However, total body irradiation (TBI) and other preparative regimens required prior to BMT have important destructive effects on the supportive cell types that orchestrate recovery of the haematopoietic process (Williams and Gress, 2008 ; Cao et al, 2011 ). Indeed, reduction of the intensity of the preparative regimens has been shown to improve bone marrow HSC engraftment as well as the subsequent reconstitution of the immune system, probably due to the better preservation of the bone marrow and thymic microenvironments (Basara et al, 2002 ; Jiménez et al, 2005 ; Calvo-Asensio et al, 2017 ). Yet, while the protection of endogenous MSCs and/or the administration of exogenous MSCs are likely to have beneficial effects improving the outcomes of allogeneic BMT and in treating GVHD (Sugrue et al, 2017 ), MSC are also known to be recruited into the tumor microenvironment (Hanahan and Coussens, 2012 ; Kidd et al, 2012 ) where they are transformed into CAFs and promote tumorigenesis through various mechanisms (Kraman et al, 2010 ; Hanahan and Weinberg, 2011 ; Cuiffo and Karnoub, 2012 ; Hanahan and Coussens, 2012 ; Kidd et al, 2012 ; Barcellos-de-Souza et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, total body irradiation (TBI) and other preparative regimens required prior to BMT have important destructive effects on the supportive cell types that orchestrate recovery of the haematopoietic process (Williams and Gress, 2008 ; Cao et al, 2011 ). Indeed, reduction of the intensity of the preparative regimens has been shown to improve bone marrow HSC engraftment as well as the subsequent reconstitution of the immune system, probably due to the better preservation of the bone marrow and thymic microenvironments (Basara et al, 2002 ; Jiménez et al, 2005 ; Calvo-Asensio et al, 2017 ). Yet, while the protection of endogenous MSCs and/or the administration of exogenous MSCs are likely to have beneficial effects improving the outcomes of allogeneic BMT and in treating GVHD (Sugrue et al, 2017 ), MSC are also known to be recruited into the tumor microenvironment (Hanahan and Coussens, 2012 ; Kidd et al, 2012 ) where they are transformed into CAFs and promote tumorigenesis through various mechanisms (Kraman et al, 2010 ; Hanahan and Weinberg, 2011 ; Cuiffo and Karnoub, 2012 ; Hanahan and Coussens, 2012 ; Kidd et al, 2012 ; Barcellos-de-Souza et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously shown that the capacity of irradiated mouse MSCs and TECs to repair DNA DSBs is modulated by hypoxia, correlating with an effect on their intrinsic radioresistance ( 34 , 40 ). Similar to the bone marrow, the thymus also consists of a hypoxic environment and therefore we were interested in investigating whether hypoxia may affect the radiobiology of DN2 thymocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies ( 69 ) have indicated that ckit is a target gene for Notch signaling. Therefore, the decrease in CD117 expression may be the result of decreased Notch ligand expression by TECs following irradiation ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies also suggest that a lower-intensity cytoreduction regimen leads to increased T cell lymphopoiesis, thus suggesting a direct link between thymus tissue damage and T cell formation. The studies described above have led to a more indepth examination of processes aimed at the mechanisms of protecting and restoring thymus and thymopoiesis tissue (38). Greater attention is drawn to this subject area within today's dynamically developing field of cancers immunotherapy, which primarily is directed to supporting and activating the natural immune response to eliminate tumours in the body.…”
Section: Utilizing Knowledge Of Effects Of Irradiation In Therapymentioning
confidence: 99%